Plasma Science Recent Advances, New Perspectives and Applications - Singh, Sukhmander (IntechOpen, 2023)
This book serves as a comprehensive guide for research scholars and postgraduate students in the field of plasma physics. It discusses Rayleigh-Taylor instabilities, solitary waves, quantum plasma, design of radiofrequency (RF) windows, use of a gyrotron in plasma physics, non-equilibrium plasma modeling, space plasma applications, and plasma diagnostics. The book also explores linear and nonlinear waves in a plasma medium.